Amelioration of Inflammatory Cytokines Mix Stimulation: A Pretreatment of CD137 Signaling Study on VSMC. (9th February 2017) - Zhong, Wei; Li, Bo; Li, Xiao Yang; Wang, Zhong Qun; Shao, Chen; Wang, Cui Ping; Chen, Rui; Yan, Jin Chuan
Abstract : Previous studies showed little CD137 expressed in normal vascular smooth muscle cells (VSMCs) and it is important to find a valid way to elevate it before studying its function. The level of CD137 was detected by RT-PCR, western blot, and flow cytometry, respectively. CD137 signaling activation was activated by agonist antibody and measured through phenotype transformation indicators and cell functions. Proteins in supernatants were detected by ELISA. The total CD137 elevates under different concentrations of CM treatment. Among these, 25 ng/ml CM treatment increases the CD137 expression mostly. However, flow cytometry demonstrates that 10 ng/ml CM elevates surface CD137 more significantly than other concentrations and reaches the peak at 36 h. At 10 ng/ml, but not 25 ng/ml CM pretreatment, the levels of phenotype related proteins such as SM-MHC, α -SMA, and calponin decrease while vimentin and NFATc1 increase, suggesting that VSMCs undergo phenotype transformation. Transwell, CCK-8 assay, and ELISA showed that the ability of VSMCs viability, migration, and IL-2 and IL-6 secretion induced by CD137 signaling was significantly enhanced by the pretreatment of 10 ng/ml CM. This research suggested that 10 ng/ml CM pretreatment is more reasonable than other concentrations when exploring CD137 function in VSMCs.